Does Campaigning on Social Media Make a Difference? Evidence From Candidate Use of Twitter During the 2015 and 2017 U.K. Elections. (October 2020) - Bright, Jonathan; Hale, Scott; Ganesh, Bharath; Bulovsky, Andrew; Margetts, Helen; Howard, Phil
Political campaigning on social media is a core feature of contemporary democracy. However, evidence of the effectiveness of this type of campaigning is thin. This study tests three theories linking social media to vote outcomes, using a novel 6, 000 observation panel data set from two British elections. We find that Twitter-based campaigning does seem to help win votes. The impact of Twitter use is small, though comparable with campaign spending. Our data suggest that social media campaign effects are achieved through using Twitter as a broadcast mechanism. Despite much literature encouraging politicians to engage with social platforms in an interactive fashion, we find no evidence that this style of communication improves electoral outcomes. In light of our results, theories of how social media are changing processes of campaigns and elections are discussed and enhanced.